2013
DOI: 10.1891/0739-6686.31.47
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity in Youth With Type 1 Diabetes

Abstract: Overweight and obesity in youth with type 1 diabetes (T1D) is now prevalent and accounts for significant health consequences, including cardiovascular complications and dual diagnosis of type 2 diabetes. Physical activity and lifestyle are modifiable and play an important role in the prevention and management of excessive weight, but it is unclear how these factors relate to overweight and obese youth with T1D. Thus, a systematic review was conducted to examine how physical activity, sedentary behavior, sleep,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 91 publications
(128 reference statements)
0
50
1
3
Order By: Relevance
“…Obesity is associated with several endocrine and metabolic comorbidities, including type 2 diabetes mellitus, hypertension, and DLP, and is considered an independent risk factor for increased mortality (5,22,24). In the present study, we found an association between overweight and DLP, however we found no correlation between BMI and poor GC or lipid profile.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Obesity is associated with several endocrine and metabolic comorbidities, including type 2 diabetes mellitus, hypertension, and DLP, and is considered an independent risk factor for increased mortality (5,22,24). In the present study, we found an association between overweight and DLP, however we found no correlation between BMI and poor GC or lipid profile.…”
Section: Discussioncontrasting
confidence: 72%
“…The etiology of obesity is multifactorial, resulting from an imbalance between caloric intake and energy expenditure associated with genetic, environmental, and behavioral factors, such as a sedentary lifestyle, imbalanced diets, and increased food intake. In addition, excessive weight gain has been observed in T1D patients undergoing intensive insulin therapy (5,19,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now becoming more evident that T2D patients also present with inflammation, earlier disease onset, and islet autoimmunity 7–11. In contrast, increased childhood obesity is seen more often in T1D patients12 and was once called juvenile diabetes. Type 1 diabetes can be detected in adult patients as well.…”
mentioning
confidence: 99%
“…The changing in life style, high carbohydrate and low exercise, was found to be the main reason of high DLP and lead to overweight and obesity [18]. Patient with T1D had high DLP level (72.5%) among young from high level of TC and LDL [12] [14] [19].…”
Section: Discussionmentioning
confidence: 99%